PENINGKATAN PEMAHAMAN KONSEP FISIKA SISWA PADA INDIKATOR INTERPRETASI DENGAN MENERAPKAN PEMBELAJARAN KONTEKSTUAL DI KELAS XI SMAN 1 GAUNG ANAK SERKA - Khairunnisak Khairunnisak; Hendar Sudrajat; Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research was to determine the improvement of students' understanding of physics concepts in the interpretation of the indicator by using contextual learning at class XI SMAN 1 Gaung Anak Serka. The expected benefits of this research was to provide alternative learning to improved students' understanding of physics concepts and maximize the performance of teachers in achieving educational goals. This research was conducted on October 2014 to February 2015. The type of this research was a quasy experimental design with Nonequivalent Control Group Design. The subjects were two classes of XI IA at SMAN 1 Gaung Anak Serka there were class XI IA 1 as a control class with 23 students and class XI IA 2 as an experimental class with 24 students. From the data obtained there were differences in absorption and gain scores between the control and experimental classes. The average of absorption experiment class was 73.26% in medium category, while the average of absorption in the control class was 50.54% that was included in the category of very low. For the average of Gain score experimental class was 0.46 that was included in the medium category, while the average of Gain score control class was 0.13 that was included in the low category. So it can be concluded that contextual learning provided the improvement on students’ understanding of physics concepts interpretation indicators at class XI SMAN 1 Gaung Anak Serka.Keywords: understanding physics concepts, interpretation indicators, contextual learning